Cytoplasmic polyadenylation in mammalian oocyte maturation. (24th November 2015) - Reyes, Juan M.; Ross, Pablo J.
Abstract : Oocyte developmental competence is the ability of the mature oocyte to be fertilized and subsequently drive early embryo development. Developmental competence is acquired by completion of oocyte maturation, a process that includes nuclear (meiotic) and cytoplasmic (molecular) changes. Given that maturing oocytes are transcriptionally quiescent (as are early embryos), they depend on post‐transcriptional regulation of stored transcripts for protein synthesis, which is largely mediated by translational repression and deadenylation of transcripts within the cytoplasm, followed by recruitment of specific transcripts in a spatiotemporal manner for translation during oocyte maturation and early development. Motifs within the 3′ untranslated region (UTR) of messenger RNA (mRNA) are thought to mediate repression and downstream activation by their association with binding partners that form dynamic protein complexes that elicit differing effects on translation depending on cell stage and interacting proteins. The cytoplasmic polyadenylation (CP) element, Pumilio binding element, and hexanucleotide polyadenylation signal are among the best understood motifs involved in CP, and translational regulation of stored transcripts as their binding partners have been relatively well‐characterized. Knowledge of CP in mammalian oocytes is discussed as well as novel approaches that can be used to enhance our understanding of the functional and contributing features to transcript CP and translational regulation during mammalian oocyte maturation. WIREs RNA 2016, 7:71–89. doi: 10.1002/wrna.1316 This article is categorized under: Translation > Translation Mechanisms RNA Turnover and Surveillance > Regulation of RNA Stability